Novel lanthanide appended hybrid hydrogel based on water-induced shape memory luminescence. Issue 4 (2nd October 2021) - Zeng, Wei; Su, Rong; Zhou, Wei; Yu, Xiaoqi; Zheng, Yuhui
ABSTRACT: The direct utilization of fluorescent signals to explore biological property or sensing performance has been extensively studied in recent years, whereas the employment of lanthanide ions as tracking agents for the shape memory process will be very rare. In this work, polyvinyl alcohol (PVA) has been attached by tryptophan and such polymeric host could bind well with both europium and terbium ions. However, the intra-molecular energy transfer efficiency was relatively low and the second ligand marbofloxacin has been incorporated. In this way, typical red and green emissions derived from europium and terbium ions are afforded. These findings lead to the systematic exploitation of polymer chain network with striking lanthanide luminescence and the detailed shape memory evolution can be recorded. In addition, such organic-inorganic hybrid hydrogel is valuable in metal management and the selective fluorescent responses to copper ions are evaluated. Therefore, the new composite exhibits potentials in signaling and determination of target species with biological or environmental importance.